Mites (Acari) associated with three species of the genus Jatropha (Euphorbiaceae) in Brazil, with emphasis on Jatropha curcas - Lofego, A. C. [UNESP]; Rezende, J. M. [UNESP]; Verona, R. L.C.; Feres, R. J.F. [UNESP] (Systematic and Applied Acarology Society, 2013)
The physic nut (Jatropha curcas L.) (Euphorbiaceae) has emerged as a new option in cultivation aimed at biodiesel production. In order to provide information that may be useful to further develop management plans for that specific crop, samples of mites were collected from cultured and wild J. curcas plants in various regions of the country and from two other species of the same genus, Jatropha gossypiifolia L. and Jatropha mollissima (Pohl) Baill. in the northeastern region of Brazil. Altogether 31 species belonging to 10 families were recorded. The family Phytoseiidae presented the largest number of species (17). Polyphagotarsonemus latus Banks (Tarsonemidae) was the most abundant species (8,503 specimens). A dichotomous key was prepared to identify all the sampled species. At least four mite species of the samples deserve attention as showing potential for being pests in the crops of J. curcas, Brevipalpus phoenicis, Brevipalpus obovatus, Polyphagotarsonemus latus and Tetranychus bastosi, the latter two often found in great abundance. © 2013 Systematic & Applied Acarology Society.
Keywords: Biodiesel production; Polyphagotarsonemus latus; Tetranychus bastosi